Development of Character Assessment Instruments for Student - I Gusti Ayu Putu Indy WismaDewi; Ni Ketut Suarni; Nyoman Dantes Dantes (Bisma The Journal of Counseling, 2020)
This study aims to develop instruments for evaluating the character of Vocational High School students as well as knowing the validity of the instrument items, and the instrument reliability of the experts and practitioners. The type of research used is research and development (R&D), the research model used is Four-D (4D). The 4D model consists of four stages of research namely define, design, develop, and disseminate. Analysis of the data used is to test the validity of manual book product content with the Lawshe CVR and CVI formulas. Tests carried out by 5 experts or experts who are competent in the field of Counseling and Psychological Guidance. The results of the study based on content validity analysis are the CVR values per item obtained between +1 to 0 (CVR> 0). Furthermore, the results of the Lawshe CVI analysis obtained a score of 0.97 greater than 0 (0.97> 0). Based on the analysis of these data means the value of the validity of the instrument content is high and for the reliability results obtained at 0.78> 0.60 thus all items of the questionnaire are declared reliable